Time is Brain: Prehospital Time for Stroke Patients in Florida. (16th November 2020) - Heemskerk, Johan; Domingo, Ricardo; Vivas-Buitrago, Tito G.M; Quiñones-Hinojosa, Alfredo; Huang, Josephine; Tawk, Rabih G; Abode-Iyamah, Kingsley; Freeman, William
Abstract: INTRODUCTION: Emergency medical services (EMS) play a critical role within the stroke system of care since prehospital care is a major component of the total time from stroke onset to reperfusion therapy and effective treatment of acute stroke is time-dependent. In an effort to limit the morbidity and mortality associated with stroke, the American Stroke Association (ASA) published time benchmarks for EMS to reduce prehospital time. METHODS: A retrospective analysis was performed using data from Florida's Emergency Medical Services Tracking and Reporting System database. All patients in 2018 with suspected stroke, transported to a treatment center, were analyzed. Time intervals from 911-call to hospital arrival were evaluated and compared to ASA benchmarks. RESULTS: In 2018, 1.8% of all 911 responses were reported as stroke by dispatch centers. After assessment at scene, 11, 577 patients with suspected stroke were transported to a hospital. Mean age was 71.5 years and 51.5% were women. The median alarm-to-hospital time was 33.98 minutes with total EMS time of 32.30 minutes. On-scene time was the largest time interval with 13.28 minutes. EMS encounters met the ASA benchmarks for time in 57.7%-62.3% (recommended 90%, P < .001). Total EMS time was reduced when a stroke notification was reported by the dispatch center (32.00 vs 32.62 min; P = .006), a stroke assessment scale was used by the EMS personnel (31.88 vs 32.96 min; P = .005) or if a stroke protocol was used to direct patient care (32.00 vs 33.30 min; P < .001). CONCLUSION: This study shows that a significant opportunity for improvement of stroke care in Florida for suspected stroke patients to help EMS encounters meet ASA benchmarks. Some prehospital EMS stroke interventions seem to reduce prehospital time and adoption of prehospital stroke screen interventions might improve the stroke systems of care.